2016
DOI: 10.1080/03091902.2016.1199743
|View full text |Cite
|
Sign up to set email alerts
|

A review of the physiological and histological effects of laser osteotomy

Abstract: Osteotomy is the surgical cutting of bone. Some obstacles to laser osteotomy have been melting, carbonisation and subsequent delayed healing. New cooled scanning techniques have resulted in effective bone cuts without the strong thermal side effects, which were observed by inappropriate irradiation techniques with continuous wave and long pulsed lasers. With these new techniques, osteotomy gaps histologically healed with new bone formation without any noticeable or minimum thermal damage. No significant cellul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 82 publications
0
24
0
Order By: Relevance
“…Only two very recent systematic reviews were found comparing rotary instruments with lasers in general [14,15], pointing out that "additional research is necessary to evaluate different laser types with appropriate laser setting variables to increase ablation rates, with control of depth, change in bone type and damage to adjacent soft tissue " [14] and "because of the lack of clinical studies, it is not possible to make a conclusive result whether there is superiority of laser osteotomy in clinical practice" [15].…”
Section: Group 1 (Systematic Reviews and Meta-analyses)mentioning
confidence: 99%
“…Only two very recent systematic reviews were found comparing rotary instruments with lasers in general [14,15], pointing out that "additional research is necessary to evaluate different laser types with appropriate laser setting variables to increase ablation rates, with control of depth, change in bone type and damage to adjacent soft tissue " [14] and "because of the lack of clinical studies, it is not possible to make a conclusive result whether there is superiority of laser osteotomy in clinical practice" [15].…”
Section: Group 1 (Systematic Reviews and Meta-analyses)mentioning
confidence: 99%
“…Thermal damage to an ablation target is a concern that is explored in multiple studies, as excessive thermally-induced necrosis will prevent or delay healing [16][17][18][19]. Ablation in the thermal regime is limited by excessive heat accumulation and diffusion into tissue.…”
Section: Topical Chromophoresmentioning
confidence: 99%
“…Over the past several years, there has been a particular interest in the development of laser surgery systems due to the advantages offered by laser-based cutting, including minimal invasiveness, noncontact interaction, precise and small cuts, functional cut geometry as well as less trauma. [1][2][3][4][5][6] Moreover, in comparison to other mechanical procedures, such as conventional surgery, bone showed faster healing after interventions with laserosteotomes. 7 Studying the effect of different laser parameters on quality and efficiency of laser cutting in both soft and hard tissues is a topic of present interest.…”
Section: Introductionmentioning
confidence: 98%